2011
DOI: 10.1038/tp.2011.10
|View full text |Cite
|
Sign up to set email alerts
|

Empirical support for an involvement of the mesostriatal dopamine system in human fear extinction

Abstract: Exposure therapy for anxiety disorders relies on the principle of confronting a patient with the triggers of his fears, allowing him to make the unexpected safety experience that his fears are unfounded and resulting in the extinction of fear responses. In the laboratory, fear extinction is modeled by repeatedly presenting a fear-conditioned stimulus (CS) in the absence of the aversive unconditioned stimulus (UCS) to which it had previously been associated. Classical associative learning theory considers extin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 53 publications
5
69
1
Order By: Relevance
“…This effect was persistent across time and contexts, was dependent on the temporal pairing of extinction with the compound, and occurred whether D1/5 activation occurred before or after extinction. Our finding of accelerated extinction and somewhat weakened contextual renewal is consistent with a finding from humans with L-dopa administration (Haaker et al, 2013), suggesting potential therapeutic efficacy in targeting dopaminergic systems in extinction (see also Raczka et al, 2011;Dubrovina and Zinov'eva, 2010). Although our experiments primarily focus on fear and reward extinction, Guarraci et al (1999) and others (Pezze and Feldon, 2004) have demonstrated that fear conditioning is also modulated by D1/5 receptor activation within specific brain regions.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This effect was persistent across time and contexts, was dependent on the temporal pairing of extinction with the compound, and occurred whether D1/5 activation occurred before or after extinction. Our finding of accelerated extinction and somewhat weakened contextual renewal is consistent with a finding from humans with L-dopa administration (Haaker et al, 2013), suggesting potential therapeutic efficacy in targeting dopaminergic systems in extinction (see also Raczka et al, 2011;Dubrovina and Zinov'eva, 2010). Although our experiments primarily focus on fear and reward extinction, Guarraci et al (1999) and others (Pezze and Feldon, 2004) have demonstrated that fear conditioning is also modulated by D1/5 receptor activation within specific brain regions.…”
Section: Discussionsupporting
confidence: 77%
“…Increases in the availability of dopamine in the synaptic cleft result in increased receptor binding and activation of multiple intracellular signaling cascades. Drugs such as methylphenidate, methamphetamine, and L-dopa appear to promote memory and extinction through this mechanism (Abraham et al, 2012;Wood and Anagnostaras, 2009;Carmack et al, 2010;Haaker et al, 2013), raising the potential for dopaminergic compounds in treating post-traumatic stress disorder (Raczka et al, 2011;Bukalo et al, 2014). Increased availability of dopamine causes activation of D1-like and D2-like dopamine receptors, but the memory-enhancing effects of dopamine receptor activation are hypothesized to be mediated by D1/5 receptors, as antagonizing D1/5 receptors blocks methylphenidate's actions on working memory (Arnsten and Dudley, 2005), and impairs consolidation of fear or reward extinction (Hikind and Maroun, 2008;Fricks-Gleason et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In support of a potentially protective role of the COMT Met 158 allele, a recent study has shown that COMT Val 158 /Val 158 homozygotes are associated with heightened reacquisition of fear from presumed alterations in reconsolidation of fearful memories [42]. Conversely, the COMT Met 158 allele has been also been associated with impaired fear extinction in some, but not all studies [60,61], and may therefore increase propensity for PTSD development in other contexts. However, a detailed review of the hypothesized mechanisms is beyond the scope of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Raczka et al (2011) found that polymorphism in the dopamine active transporter 1 gene DAT1 predicted faster extinction learning in healthy humans. In a study of 60 healthy individuals, Huertas et al (2010) found that a polymorphism in the DRD2 dopamine receptor D2 gene predicted significantly attenuated SCR during early conditioning.…”
Section: 1 Conditioning and Extinction In Ptsdmentioning
confidence: 99%
“…Furthermore, in their study the Met allele was associated with decreased vmPFC activation and increased amygdala activation during extinction. Another study reported inconsistent data in that homozygous Val-carriers showed heightened SCR to both conditioned and unconditioned cues during reconditioning of a previously extinguished association (Raczka et al, 2011). Given the role of BDNF in hippocampal-dependent processes (Tyler, Alonso, Bramham, & Pozzo-Miller, 2002) as well as fear and anxiety (Frielingsdorf et al, 2010), future research may emphasize contextual fear conditioning to better elucidate the role of the Val66Met SNP of BDNF .…”
Section: 1 Conditioning and Extinction In Ptsdmentioning
confidence: 99%